Cultural Adaptation of Screening, Brief Intervention and Referral to Treatment Using Motivational Interviewing. Issue 5 (September 2015) - Satre, Derek D.; Manuel, Jennifer K.; Larios, Sandra; Steiger, Scott; Satterfield, Jason
Abstract : This clinical case presentation and discussion illustrates a culturally adapted alcohol and drug use intervention using the Screening, Brief Intervention, and Referral to Treatment (SBIRT) approach, incorporating motivational interviewing skills. This case conference serves to complement the accompanying review article on SBIRT with diverse cultural groups, placing information from the review in the context of a typical clinical setting. In this example, SBIRT is provided in a primary care clinic to a Latino patient who reports hazardous drinking, depression, chronic pain and use of prescription opioids.